ADAPTATION OF NURSING STUDENTS LIVING IN STUDENT DORMITORY - Maria Frani Ayu Andari Dias; Gita Permata Hatika; Anastasia Maratning (Jurnal Keperawatan Dirgahayu (JKD), 2023)
Abstract There are not many research results that discuss the adaptation of nursing students to their place of residence, namely in the dormitory. This initial research aims to explore the potential of conducting research on nursing students living in dormitories, including the potential for conducting research related to adaptation. This research was conducted descriptively by applying cross-sectional data collection. The data was then analyzed and presented in the form of frequency distribution tables and narratives. The results of the study indicate that study in a broader and more in-depth scope needs to be carried out to capture the unique and important conditions in the adaptation period of nursing students living in dormitories. The ability of students to adapt quickly and well to their place and environment will be an important capital in the process of forming them into skilled and agile nurses. Abstrak Tidak banyak catatan-catatan hasil penelitian yang membahas tentang adaptasi mahasiswa/I keperawatan di tempat tinggal mereka, yaitu di asrama. Penelitian awal ini bertujuan untuk menelusuri potensi pelaksanaan penelitian pada mahasiswa/I keperawatan yang tinggal di asrama, yang termasuk didalamnya adalah potensi untuk melakukan penelitian terkait adaptasi. Penelitian ini dilakukan secara desktiptif dengan menerapkan pengambilan data secara potong lintang. Data selanjutnya dianalisis dan disajikan dalam bentuk tabel distribusi frekuensi dan narasi. Hasil penelitian menunjukkan bahwa penelitian dalam cakupan yang lebih luas dan dalam perlu dilakukan untuk menangkap keadaan unik dan penting dalam masa-masa beradaptasi mahasiswa/I keperawatan yang tinggal di asrama. Kemampuan mahasiswa/I untuk beradaptasi dengan tempat dan lingkungannya dengan cepat dan baik akan menjadi modal penting dalam proses pembentukkannya sebagai seorang perawat yang terampil dan tangkas.